The impact of financial leverage to Profitability Study of Non-Financial Companies Listed in Indonesia Stock Exchange - , M. Shalahuddin Mustofa El-Wahid; , Su'ad Husnan, Dr., MBA. ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Debt is used by many companies to leverage their capital and profit. However, debt is not the only factors that effect to leverage capital and profit. There are several factors that can affect the companiesâ profitability. This research uses operational decision factor, macroeconomics factor, firm size factor, and industry factors to help understand the effect of debt to profitability. Operational decision factor is proxy by total assets turnover to explain how well the companies able to utilize their assets to generate profit. Firm size factor is proxy by assets to measure the companiesâ power to generate profit. While macro economics factor is proxy by BI rate because it can represent the inflation effect and the impact to the bankâs interest rate. The uniqueness of this research is to add industry factor to compensate the other factors in determining the companiesâ profitability. There are 336 samples from 48 companies in eight industries observed from 2003 to 2009 used in this research. The samples taken are determined by listing the lowest and highest profitable companies on each different industry. The test is made to the whole samples and to each different industry to examine the general effect and the industry effect of debt, operational decision, firm size, and macroeconomics to companies. The result indicates that in uncategorized (not categorized into different industries) data, debt, firm size, and operational decision effect positively significant, and macroeconomics effect insignificantly towards profitability. However, if the data is tested based on the industry, the result varies depend on the industry. This indicates that industry factor do effect companiesâ profitability.